Pola Perilaku Penelusuran Informasi di Kalangan Mahasiswa yang Sedang Menyelesaikan Tugas Skripsi - Humaira, Intan; Ananda, Elisa; Nurhumairoh, Siti; Kamil, Insan; Purwaningtyas, Franindya (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
The goal of this study is to identify the information-seeking patterns of students who are working on their final projects. Students in their last year require a lot of reading materials, both printed and unprinted. Additionally, the sources used ought to be reliable and trustworthy. According to the person conducting the information search, which is decided by the information demands of each individual, information seeking behavior is established. Research undertaken through data collecting, scientific writing that results in research items or library data gathering, or research conducted to solve a problem that is mostly based on critical and in-depth studies constitutes the sort of research used in this study. Keywords: Pattern, Behavior, Search, Information